Features of the economic and social assessment of projects for establishing construction industry enterprises in the context of recovery - PALAHITSKYI, Viktor; KAZMIN, Oleksandr; KOSHOVY, Bohdan; SHOKOTKO, Oleksiy; HORBENKO, Serhiy (Ways to Improve Construction Efficiency, 2025)
The article examines the features of the economic and social assessment of projects for establishing construction industry enterprises in the context of Ukraine’s national economic recovery. The relevance of the topic is driven by large-scale infrastructure destruction, the urgent need for rapid modernization of the construction industry, and the growing importance of the social impacts of investment decisions. It is substantiated that traditional evaluation methods focused exclusively on financial indicators (NPV, IRR, PI, payback period) do not provide a comprehensive understanding of project performance in post-crisis conditions, as they fail to account for their impact on employment, community development, social stability, and the environmental sustainability of territories. The paper summarizes the approaches of Ukrainian and international scholars regarding the incorporation of behavioral, social, and environmental factors into the investment analysis process. It is demonstrated that construction industry enterprises play a crucial role in generating a multiplier effect in the labor market, contributing to the development of local infrastructure and stimulating economic activity in regions affected by hostilities. Particular attention is given to assessing the social significance of projects, which includes analyzing job creation, wage levels, working conditions, opportunities for professional training, and the integration of internally displaced persons and veterans. Environmental criteria are identified as an essential component of the assessment, as compliance with them is a prerequisite for attracting international financing. The study outlines key ESG requirements for construction industry enterprises, particularly in terms of energy efficiency, emission reduction, the use of secondary resources, and environmentally safe placement of production facilities. Based on the conducted analysis, the authors substantiate the need to develop a comprehensive multi-criteria methodology for the economic and social assessment of projects aimed at establishing or relocating construction industry enterprises. The proposed approach makes it possible to account for economic feasibility, social benefits, environmental constraints, logistical risks, and regional priorities. This ensures a more accurate and objective determination of project effectiveness, supports the optimal allocation of resources, and enhances the resilience of reconstruction processes.